THE EFFECT OF WORK STRESS AND WORK ENVIRONMENT ON EMPLOYEE PERFORMANCE IN PUBLIC WORKS AND SPATIAL PLANNING (DPUPR) KARAWANG DISTRICT - Fikiana (Journal Of Resource Management, Economics And Business, 2026)
Purpose: This study aims to examine the effect of work stress and work environment on employee performance at the Public Works and Spatial Planning Office of Karawang Regency. Research Methodology: This study used a quantitative verification approach with a survey method. Primary data were collected through questionnaires using a five-point Likert scale. The population consisted of 100 employees, and all members of the population were selected using a saturated sampling technique. The data were analyzed using IBM SPSS Statistics 26 through validity testing, reliability testing, classical assumption testing, multiple linear regression, t-test, F-test, and coefficient of determination analysis. Results: The results show that work stress has a negative and significant effect on employee performance, with a regression coefficient of -0.339 and a significance value of 0.001. Meanwhile, the work environment has a positive and significant effect on employee performance, with a regression coefficient of 0.574 and a significance value of 0.000. Simultaneously, work stress and work environment significantly affect employee performance, with an R-square value of 0.837, indicating that 83.7% of employee performance variation can be explained by the two independent variables. Limitations: This study is limited to one public sector institution and uses cross-sectional self-reported data. Contribution: This study contributes to human resource management studies, especially in explaining how work stress and work environment influence employee performance in local government institutions.